TOBACCO INDUSTRY LABOR MANAGEMENT COMMITTEE GENERAL LEDGER REPORT - CURTIS,R (Tufts Archival Research Center, 2007)
Marginalia; General Ledger Report for Labor Management Committee (LMC) for 1995. Lists Tobacco Institute contributions. Includes calculator tape summing contributions.